Experiment and insitutionalization - Brogan, Michael J. (Lex localis, 2009)
There is not a general consensus among scholars about whether public campaign funding initiatives increase electoral competitiveness. U.S. focused research has found the effects of Clean Election (CE) funding present mixed outcomes (Mayer and Wood 1995, GAO 2003, Mayer, Werner, and Williams 2004, Werner and Mayer 2007) on the one hand, research has found that Clean Election funding creates more competative elections (Bardwell 2002, Mayer, Werner, and Williams 2004). While on the other, Clean Election funding scholars have found that public funding of state legislative candidates has not caused elections to become more competitive (mayer and Wood 1995, GAO 2003). One reason for the difference in the research literature is likely a result of the program being in its early years of implementation in the U.S. This paper provides a new technique for estimating the short-term and long-range effects of the program by experimenting on the New Jersey case which is designed to cope with limited data. It accomplishes this by creating simulated elections that are based on the lessons-learned in Arizona and Maine, as well as on structural constraints present in New Jersey. The experiment's results confirm the impact of Clean Election is mixed. The impact of Clean Election funding increase intra-party competition but does not increase inter-party competition. Nevertheless, while the impact of Clean elections does show some encouraging signs for proponents of electoral reform, it is unlikely to transform the electoral landscape by making elections more competitive.
Keywords: New Jersey; politične stranke; predvolilna kampanja; volitve; ZDA